ANALISIS PERBEDAAN KONSEP ZAKAT DAN INFAK DALAM ALQUR’AN - Adina Litriwani; Elma Fiisma Dalimunthe; Aditya Putra Piliang; M. Farhan Aulia Rozan; Roza Aulia; Ferizal (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
The Qur'an, through a series of verses, also lays down a series of basic norms for several types of transactions, both general and specific. Including basic norms related to several types of economic transactions. Therefore, the absorption of the text of the Qur'an into a compilation of laws including economic and financial verses against the compilation of laws in the field of Sharia economics, textually will certainly experience difficulties, but substantially based on the istinbath of the law (istinbath al-ahkam) from the existing verses of economic law, it is very possible. The possibility of the compilation of the text of the Qur'an being absorbed into the compilation of the field of Sharia economics, depends greatly on the compilation model itself. Islam guarantees a distribution of income that contains human values, namely, among others, Islam recommends distributing wealth through zakat, infaq, and others in order to maintain harmony in social life. Infaq and zakat can be used to open up job opportunities in the form of capital assistance, education, health facilities and so on, so that it will be more productive. This study aims to discuss zakat and infaq from the perspective of the Qur'an.